A unilateral thalamic lesion referred for biopsy: Answer. (June 2020) - Borg, Anouk; Hill, Ciaran Scott
Highlights: Venous thrombosis of the great cerebral vein can lead to thalamic infarction. Venous infarction can have similar MR imaging appearance to a space occupying lesion. CT venography or gadolinium-enhanced MR venography is the most frequently used technique to show venous thrombosis.